Analisis Jaminan Hak-Hak Pekerja Pada PT. Mas Murni Indonesia (Hotel Garden Palace Surabaya): Studi Kasus Putusan MAHKAMAH AGUNG Nomor 1565 K/Pdt.Sus-PHI/2022 - Gibran, Rizal Ananda; Putra Siagian, Imanuel Nelson; Purba, Moses Frederick (Media Hukum Indonesia (MHI), 2024)
Hotel Garden Palace Surabaya, operated by PT MAS MURNI INDONESIA, declared bankrupt by the Surabaya Commercial Court, conducted mass layoffs without paying severance to approximately 200 employees. According to Law Number 13 of 2003 concerning Manpower, even if a company is declared bankrupt, the curator must continue business operations and fulfill obligations like salary payments. The Industrial Relations Court has absolute authority to resolve labor disputes, including rights disputes, interest disputes, and termination disputes. Workers who were unilaterally laid off by Hotel Garden Palace Surabaya can file a lawsuit with the Commercial Court based on Article 153 of the Manpower Law. Factors affecting the effectiveness of the Industrial Relations Court include the involvement of related parties, the competence of judges, resource limitations, and the involvement of mediation institutions. The implementation of dispute resolution mechanisms through the Industrial Relations Court significantly impacts workers' rights, employers' obligations, and the industrial relations climate. The court ensures proper compensation for workers who are unilaterally laid off and provides legal protection, ultimately increasing workers' confidence in their rights and stabilizing industrial relations at Hotel Garden Palace Surabaya. In conclusion, the Industrial Relations Court plays an essential role in enforcing labor laws and ensuring protection and justice for laid-off workers, even in situations of company bankruptcy.